Comparative analysis of phraseological units with the somatic component 'Head' in English and in Armenian - Hayrapetyan, Saida (Լիմուշ հրատ.)
This paper has attempted to show that Armenian and English idiomatic expressions containing the somatic component ‘head’ are motivated by cognitive strategies such as general conventional knowledge of the world and conceptual metaphors and metonymies which underlie the figurative meaning of these idioms. The claim that idioms are motivated by three cognitive strategies, i.e. general conventional knowledge and conceptual metaphors and metonymies, has been tested on a number of idioms in both Armenian and English. Այս հոդվածը փորձել է ցույց տալ, որ հայերեն եւ անգլերեն դարձվածքները, որոնք պարունակում են «գլուխ» բաղադրիչը, հիմնավորվում են պատկերավորման արտահայտչական միջոցներով, ինչպիսիք են` աշխարհընկալման ավանդական գիտելիքները, փոխաբերությունները եւ փոխանունությունները, որոնք ընդգծում են դարձվածքների փոխաբերական իմաստները: Այն պնդումը, որ դարձվածքները հիմնավորվում են երեք ճանաչողական միջոցներով` ավանդական գիտելիքներով, փոխաբերություննե րով եւ փոխանունություններով, փորձարկվել է մի շարք դարձվածքներում` հայերեն եւ անգլերեն: В данной статье была предпринята попытка показать, что армянские и английские фразеологические единицы с соматическим компонентом "голова" мотивированы познавательными подходами такими как общепринятое знание, концептуальные метафоры и метонимии, лежащие в основе образных значенияи этих идиом. Утверждение, что идиомы мотивированы тремя познавательными стратегиями, то есть общие традиционные знания и концептуальные метафоры и метонимии, было протестировано на ряде идиом в армянском и английском языках.
Keywords: Linguistics